RASIONALITAS AMERIKA SERIKAT DALAM PERJANJIAN DAMAI DENGAN TALIBAN PASCA KONFLIK DI AFGANISTAN - Ayu Suwari, Ni Wayan; Sushanti, Sukma; Parameswari, A.A. Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
The US invasion of Afghanistan was motivated by the unwillingness of the Taliban regime in Afghanistan to hand over Al-Qaeda, which was the perpetrator of the 9/11 attacks, to the US. After 18 years of invasion, the US carried out a reorientation of foreign policy in Afghanistan in the form of a Peace Agreement with the Taliban. This study then attempts to analyze the reasons for the formation of the US peace agreement with the Taliban using the rational actor model and the supporting concept of retrenchment strategy. This study was analyzed using an explanatory-qualitative methodology sourced from secondary data. The result of this study is that the US entered into a peace agreement to stop massive losses due to the invasion in the form of material and troop crises. This can be achieved at the expense of US interests in Afghanistan. Keywords: United States of America, Taliban, Peace Agreement, Rationality